Assessing the effectiveness of risk management practices used by contractors in South African construction - Chiswanda, Farai (Department of Construction Economics and Management, 2022)
This research examines the risk management practices prevalent in the South African construction industry. This was necessitated by the dearth in effective risk management in the construction industry particularly in developing countries such as South Africa. A comprehensive literature review was conducted to establish the risk management practices in use. Based on the literature, a questionnaire was developed and administered electronically to contractors operating in South Africa. The study established that contractors face a significant number of risks, chief among them, high competition in bids, political instability, payment delays, corruption and bribery and an overbearing influence of bureaucratic processes from government aligned agencies. Furthermore, it was also established that risk management amongst South African contractors is largely informal due to a mediocre appreciation of risk management. It also emerged that risk management implementation is perceived to be an expensive venture that erodes the marginal profits contractors aim to make. Resultantly, risk management practices implementation is low amongst the contractors. Based on the findings, the study concludes that the South African construction industry suffers from ineffective risk management implementation. To improve the implementation of risk management practices amongst contractors, it is recommended that contractors increase their risk management awareness through risk management training and risk knowledge management. Overall, this will be beneficial for their operations as risk management has been found to yield a positive effect on the meeting of project objectives. Furthermore, private and public sector clients are also encouraged to demand evidence of risk management competency from contractors upon engaging them for work.